HUBUNGAN KEBIASAAN MAKAN DAN IMT/U DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI DESA SIRNAGALIH - Jovanka Adina, (2022)
In Indonesia, the incidence of anemia in women of productive age is categorized as moderate and continues to increase every year. Anemia can cause various disadvantages such as delayed growth and development, increased susceptibility to infection, and in pregnant women can increase the risk of premature birth, low birth weight also mother and child mortality. This study aims to analyze the relationship between eating habits and IMT/U on the incidence of anemia. The research was conducted in Sirnagalih Village with a cross-sectional research design. The sampling technique was purposive sampling with a sample of 74 female respondents aged 10-18 years. Anemia is measured with a Portable Hemoglobinometer by looking at hemoglobin levels. IMT/U data were obtained through anthropometric measurement. Intake of protein, vitamin C, and iron minerals using a 1x24h recall interview. Frequency of Fe enhancers and inhibitors by interviewing with Food Frequency Questionnaire. Bivariate analysis using Spearman Rank. The results of statistical tests showed that there was no relationship between IMT/U (p = 0.440), Intake of protein (p = 0.813), iron (p = 0.911) and vitamin C (p = 0.630), the frequency of iron enhancers (p = 0.618), and iron inhibitors (p= 0.350) on the incidence of anemia in adolescent girls in Sirnagalih Village. Adolescent women are expected to regulate eating habits according to balanced nutrition and control body weight.